Perancangan Ulang Tata Letak Warehouse guna Perbaikan Letak Produk Jadi Kemasan (Studi Kasus: PT GRAFIKA PRIMA SEJAHTERA) - Rahmah, Bella Shefia; Siti, Mundari (Universitas Bojonegoro, 2023)
PT. Prima Sejahtera Graphics prints various packaging types, including pharmaceutical, food, and beverage packaging. The current storage policy assigns fixed pallet areas for each product type, causing inefficiencies when pallet space does not match output volume. This mismatch complicates warehouse operations and is worsened by carriers returning goods based on packaging configurations. Consequently, warehouse staff face increased workload managing inbound and outbound flows. To resolve this, the study proposes a shared storage system allowing flexible placement by product type. This method optimizes space use and reduces unnecessary movement. Implementation results show a reduction in travel distance from 418.5 meters to 395.5 meters, demonstrating improved operational efficiency.